Catalog of the Acari types deposited in the American Museum of Natural History, New York (Arthropoda: Arachnida) - Hernandes, Fabio A.; Huff, Jeremy C.; Oconnor, Barry M. (Zootaxa, 2011)
A catalog of the type specimens of Acari representing 45 families, 153 genera and 377 species deposited at the American Museum of Natural History is presented. Additional material from the original type series deposited in other institutions is also noted. Where possible, the host is indicated.